Dívida pública brasileira 1995-2005: alongamento e perfil de indexação - Siqueira, Jorge Cesar (2007)
ABSTRAT The purpose of this study is to present and discuss the main impacts the indexation profile and the term-structure of the public debt may inflict on the debt´s trajectory. The main result of the study suggests that there may exist a vicious circle stemming from the relationship between the rise of the short-term interest rate of the Brazilian economy and the growing-path behavior of its public debt. It is stated that this movement may be a consequence of the uniqueness of the structure of Brazilian public debt, which is largely composed by short-term securities pegged to the short-term interest rate of the economy (Selic). In order to demonstrate this statement, the approach taken up rests on two models of public debt administration and on the analysis of these models in reference to the behavior of the level and the profile of indexation and term-structure of the public debt between 1995 and 2005. Therefore, our effort seeks to present the workings of this supposed vicious circle and its impacts on the behavior of the Brazilian public debt. In addition, in order to estimate exercises which may, at some length, corroborate the main idea proposed by this study, we make use of some econometric tools, such as Vector auto-regressions models and Vector Erros Corretions